A retrospective study on the causes for evisceration at Tilganga Eye Centre - Limbu, B; Saiju, R; Ruit, S (Kathmandu University Medical Journal, 2010)
Background: Evisceration is one of destructive surgery of eye after which a patient loses his hope of restoration of sight forever. Aim and objectives: To identify the major causes of evisceration at a tertiary eye centre of Nepal. Materials and methods: This is hospital based retrospective study of patients presented at Tilganga eye centre, Kathmandu, Nepal over a period of two years (10 Nov 2004 to 10 Nov 2006). Out of 2,31,976 total OPD patients, 71 patients who had evisceration with or without implant were selected and finally, only 67 patients record were enrolled for study as data were insufficient in the remaining records to fill up the study format. Data processing and analysis done using computer SPSS 11.5. Results: A total of 67 cases, with age ranging from 1.5 years to 85 years, out of which 33 male and 34 were female. Evisceration was performed most commonly due to trauma and it's subsequent sequele in 37 cases (55.2% of total cases), who were within the age group of 30 - 59 years (p = 0.033) and predominantly male 25 cases(p = 0.001). Most of the patients presented from outside Kathmandu valley, with visual acuity of no perception of light. Conclusion: Evisceration without implant was most common surgical procedure, with trauma being the leading cause for it and most of the trauma was seen in active, potential and young male patients. So prevention of ocular injuries together with early treatment protocol is best way to decrease the rate of evisceration due to ocular trauma. To prevent ocular injuries news paper, television and health education may play an important role. Key words: Ocular trauma; destructive surgery; evisceration. DOI: 10.3126/kumj.v7i2.2702 Kathmandu University Medical Journal (2009) Vol.7, No.2 Issue 26, 115-119